Targeted Business Incentives and the Debt Behavior of Households - Wenhua Di; Daniel L. Millimet (Institute for the Study of Labor (IZA), 2016)
The empirical effects of place-based tax incentive schemes designed to aid low income communities are unclear. While a growing number of studies find beneficial effects on employment, there is little investigation into other behaviors of households affected by such programs. We analyze the impact of the Texas Enterprise Zone Program on household debt and delinquency. Specifically, we utilize detailed information on all household liabilities, delinquencies, and credit scores from the Federal Reserve Bank of New York Consumer Credit Panel/Equifax, a quarterly longitudinal 5% random sample of all individuals in the US with a social security number and a credit report. Identification of the causal effect of the program is achieved using a sharp regression discontinuity approach that exploits the known institutional rules of the program.
Keywords: C21; G02; H25; H31; 330; enterprise zones; debt; consumer finance; regression discontinuity